Breeding of wheat cultivars at the Centro Nacional de Pesquisa de Trigo - period from 1986 to 1990 - N. A. de Sousa, Cantídio; P. Gomes, Edar; C. S. Moreira, João; F. Sartori, João; de J. A. Del Duca, Léo; L. Scheeren, Pedro; dos A. e Silva, Sérgio; I. Linhares, Walesca (Pesquisa Agropecuaria Brasileira, 1998)
Several wheat breeding projects have been conducted at Embrapa-Centro Nacional de Pesquisa de Trigo (CNPT), in Passo Fundo, RS, Brazil. This paper refers to the general or conventional wheat breeding project during the period from 1986 to 1990. Cultivar collections and segregating materials were evaluated and selected mainly under field conditions in Passo Fundo, RS. Advance of generations was established in Brasília, DF, and in Ciudad Obregón, México. From 1685 to 2491 plots per year of collections organized at CNPT or received from México (CIMMYT), from the United States (Nebraska and Oregon University) or from Paraguay (LACOS) were evaluated. The major activity in the project consisted of the management of segregating material in several generations until obtaining homozygous lines that, once grouped, were tested in yield trials and multiplied. Part of the segregating material was conducted using the pedigree system and other part using the bulk method. A total of 777 different crosses were done resulting in an average of 159 new lines grouped every year. Cultivars Trigo BR 16-Rio Verde, Trigo BR 19, Trigo BR 21-Nhandeva, Trigo BR 22, Trigo BR 23, Trigo BR 28, and Trigo BR 32 were bred through the project and released to farmers between 1986 and 1990. Specific traits selected in the program, such as plant height, lodging resistance, straw strength, spike type, cycle, resistance to aluminum toxicity, disease resistance (powdery mildew, leaf rust, stem rust, glume blotch, spot blotch, scab, and soil borne wheat mosaic virus), and industrial quality are discussed.